Shorter versus longer recovery periods between knock-out races in sprint cross-country skiing - McGawley, K.; Van Waerbeke, C.; Westberg, K.-J.; Andersson, E. (Sport and Fitness Sciences, 2020)
Purpose: The aim was to compare the physiological and performance effects of longer versus shorter recovery periods between the three knock-out races of a simulated sprint XC ski competition.